ICTV Virus Taxonomy Profile: Adenoviridae 2022. (9th March 2022) - Benkő, Mária; Aoki, Koki; Arnberg, Niklas; Davison, Andrew J.; Echavarría, Marcela; Hess, Michael; Jones, Morris S.; Kaján, Győző L.; Kajon, Adriana E.; Mittal, Suresh K.; Podgorski, Iva I.; San Martín, Carmen; et al.
Abstract : The family Adenoviridae includes non-enveloped viruses with linear dsDNA genomes of 25–48 kb and medium-sized icosahedral capsids. Adenoviruses have been discovered in vertebrates from fish to humans. The family is divided into six genera, each of which is more common in certain animal groups. The outcome of infection may vary from subclinical to lethal disease. This is a summary of the ICTV Report on the family Adenoviridae, which is available at ictv.global/report/adenoviridae .